The Effect of Frailty on Quality of Life in Older Patients Receiving Hemodialysis and Associations With Fear of Falling - Ozer, Zuelfuenaz; Turan, Guelcan Bahcecioglu; Basak, Seda (Wiley, 2025)
Purpose This study investigated the effect of frailty and avoidance behavior due to fear of falling on the quality of life in older patients receiving hemodialysis treatment. Methods This study is cross-sectional and descriptive. The study was conducted between January 2 and 31, 2022, with 154 individuals aged 65 years and over receiving treatment in dialysis centers. The study data were collected using the Patient Information Form, Edmonton Frail Scale, Fear of Falling Avoidance-Behavior Questionnaire, and Quality of Life Scale (SF-12). Results The Mean Edmonton Frail Scale score was found to be 8.7 +/- 3.36, the mean Fear of Falling Avoidance-Behavior Questionnaire score was found to be 33.17 +/- 9.11, the mean SF-12 physical component score was found to be 34.32 +/- 8.51, and the mean mental component score was seen as 41.77 +/- 8.35. The Fear of Falling Avoidance-Behavior Questionnaire was an associated factor in the effect of the Edmonton Frail Scale on quality of life. It strengthened the negative impact of the Edmonton Frail Scale on quality of life. The predictive effect of these two variables in explaining quality of life was 59.3%. Conclusion It was found that the participants had moderate levels of frailty, moderate levels of activity limitation, and participation restriction due to fear of falling, and low levels of physical and mental quality of life. It was determined that frailty had a direct impact on quality of life. Also, the indirect effect of frailty on quality of life was determined through the role of avoidance behavior due to fear of falling.
Keywords: avoidance behavior; fear of falling; frailty; hemodialysis; quality of life